Role of Zakat as Social Finance Catalyst to Islamic Banking and Economic Growth - Ai Nur Bayinah (Center of Strategic Studies (PUSKAS) BAZNAS, 2017)
This paper is aimed to assess the contribution of Zakat in boosting Islamic banks’ financing and economic growth for the period 2011-2015, in 10 district/city of West Java Province, Indonesia. Through Vector Autoregressive (VAR) panel co-integration analysis, variance decompositions (VD) and impulse response functions (IRF), this study investigates Zakat, Islamic Banking, and economic growth nexus. Findings in this research highlight that Zakat has a significant impact on Islamic banking, so this institution would contribute to economic growth both in the short and the long run, with fluctuation in variance from the first year. The results lend support to the view that Zakat not only leads to social benefits but also has a positive impact on the economy through increasing Islamic banks’ financing. Therefore, this research will serve as a motivation for the industry players and regulators to continuously promote Zakat as a strategic policy. The originality of this research is to assess Zakat-led growth and finance by analyzing the impact of Zakat on the Islamic banking and regional economic outcome. Another novel aspect of this study is in the methodology as it employs VAR panel co-integration analysis, VDs and IRFs on the set of annual data. Keywords: Zakat, Islamic Banking Financing, Economic Growth, West Java